An insight into the ecological risks and mitigation of heavy metal pollution in aquatic sediments and marine ecosystems - Karmakar, Kanchan; Bhattacharjee, Bhaswati; Kabir, Ayesha; Haldar, Shyamalina (Frontiers in Bacteriology, 2026)
Aquatic ecosystems are important ecological and socioeconomic zones throughout the world. However, a massive deterioration in the functionality of aquatic zones has been observed globally in recent times due to an enormous rise in environmental pollution with an ever-increasing human population, urbanization, land reformation, and industrialization. However, there is a lack of studies assessing aquatic and sediment pollution and their effects on biogeochemical cycling, the food chain, and the overall wellbeing of species, including humans. Thus, there is an immediate necessity to investigate the status of aquatic sediment pollution, evaluate the associated ecological risks, and estimate the probable pollution sources. Therefore, this review enlightens on the composition, concentrations, sources, and spatial patterns of the distribution of heavy metals affecting the global aquatic sediment pollution; their probable toxic effects on aquatic ecosystems; the modes of transfer through food chains, thereby affecting human health; and the use of aquatic plants for phytoremediation of heavy metals in aquatic ecosystems. This will lead to an understanding of the status and the factors influencing aquatic sediment pollution, which will be useful to monitor and manage the vast aquatic ecosystems and develop strategies for remediation in the near future.